2001
DOI: 10.1086/323494
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Remnant Speckles in an Adaptively Corrected Imaging System

Abstract: Adaptive correction on large ground-based telescopes is enabling a variety of novel studies that would be impossible at the limits of spatial and spectral resolution imposed by the Earth's turbulent atmosphere. Even relatively high-order systems, however, do not yield a perfect correction and as a result are compromised by a low-intensity halo of remnant light that is removed from the core of the point-spread function (PSF) and dispersed in the focal plane. Worse still, this halo is neither constant in time no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 13 publications
3
72
0
Order By: Relevance
“…Linearization of the complex quantity in the pupil plane is put forward to account for the speckle symmetry. A similar reasoning is presented by Bloemhof et al (2001) to explain the "speckle pinning effect." The FQPM can take advantage of this welcoming effect with a centrosymmetrical subtraction and yield a higher S/N than others coronagraphs.…”
Section: Resultssupporting
confidence: 61%
“…Linearization of the complex quantity in the pupil plane is put forward to account for the speckle symmetry. A similar reasoning is presented by Bloemhof et al (2001) to explain the "speckle pinning effect." The FQPM can take advantage of this welcoming effect with a centrosymmetrical subtraction and yield a higher S/N than others coronagraphs.…”
Section: Resultssupporting
confidence: 61%
“…Aime & Soummer (2004) and Soummer et al (2007a) have shown that the speckle noise from "pinned" speckles (Bloemhof et al 2001;Sivaramakrishnan et al 2002;Bloemhof 2003;Perrin et al 2003) can be reduced with a coronagraph. The variance of the speckles and photon noise in a coronagraphic image is given by…”
Section: Impact Of Chromaticity On Contrast Performancementioning
confidence: 99%
“…Residual mirror polishing errors (which tend to be rotationally symmetric anyway) and aberrations downstream the optical system are modulated by the symmetry of the Airy pattern in the small-aberration regime. "Pinned speckles" [6,16] form an additional rotationally symmetrical component in the focal plane because they are modulated by the Airy pattern. All of these effects contribute to confusion when trying to identify planets among many objectlike features, having the same spatial scale ( / D λ -the wavelength divided by the aperture width) and shape.…”
Section: Symmetry and The Imagementioning
confidence: 99%